Optimization of Hypothermic Storage of Canine Erythrocytes: the Role of Acetylcysteine in Increasing Mechanical Stability - Hrebeniuk, Karyna; Denysova, Olha (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):297